Irisin restrains neuroinflammation in mouse experimental autoimmune encephalomyelitis via regulating microglia activation - Zhang, Qiu-Xia; Zhang, Lin-Jie; Zhao, Ning; Yang, Li (Frontiers in Pharmacology, 2025)
IntroductionMultiple sclerosis is a chronic autoimmune demyelinating disorder predominantly affecting the white matter of the central nervous system, with experimental autoimmune encephalomyelitis (EAE) serving as its classical animal model. Irisin, a glycosylated protein derived from the proteolytic cleavage of fibronectin type III domain-containing protein 5, plays a significant role in metabolic regulation and inflammatory modulation within the organism.MethodsIn this study, we systematically investigated the therapeutic effects and underlying mechanism of Irisin on EAE and BV2 microglial cells through comprehensive methodologies including quantitative real-time polymerase chain reaction, immunofluorescence staining and western blot.ResultsIrisin exerts neuroprotective effects in EAE mice, significantly ameliorating both clinical and pathological manifestations of the disease. Mechanistically, Irisin attenuated inflammatory response and reduced the number of microglia through NF-κBp65 signaling pathway.ConclusionIn conclusion, these results collectively suggest that Irisin alleviates EAE progression by suppressing microglia activation via the NF-κBp65 pathway, highlighting its potential as a promising therapeutic target for multiple sclerosis treatment.